The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/ils-06-2022-0076
|View full text |Cite
|
Sign up to set email alerts
|

Representational scaffolding in digital simulations – learning professional practices in higher education

Abstract: Purpose To advance the learning of professional practices in teacher education and medical education, this conceptual paper aims to introduce the idea of representational scaffolding for digital simulations in higher education. Design/methodology/approach This study outlines the ideas of core practices in two important fields of higher education, namely, teacher and medical education. To facilitate future professionals’ learning of relevant practices, using digital simulations for the approximation of practi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…As highlighted by Braunstein et al (2022), especially social processes in simulation-based learning seem underrepresented in current research. However, since many professional practices involve a social dimension-physicians' interactions with patients, teachers' interactions with students, or collaborations between coworkers of any profession (see Fischer et al, 2022)-social processes are a highly relevant aspect of learning to perform these professional skills. In addition, considering, for example, vocational education at the 13 workplace or the internships of higher education students, professional learning in real professional settings involves social interactions with trainers or more advanced professionals-who offer explanations, modeling, and feedback-as well as social interactions with peer learners.…”
Section: From a Status Quo To A Quo Vadis In Researching Simulations ...mentioning
confidence: 99%
See 2 more Smart Citations
“…As highlighted by Braunstein et al (2022), especially social processes in simulation-based learning seem underrepresented in current research. However, since many professional practices involve a social dimension-physicians' interactions with patients, teachers' interactions with students, or collaborations between coworkers of any profession (see Fischer et al, 2022)-social processes are a highly relevant aspect of learning to perform these professional skills. In addition, considering, for example, vocational education at the 13 workplace or the internships of higher education students, professional learning in real professional settings involves social interactions with trainers or more advanced professionals-who offer explanations, modeling, and feedback-as well as social interactions with peer learners.…”
Section: From a Status Quo To A Quo Vadis In Researching Simulations ...mentioning
confidence: 99%
“…In higher education and professional training, simulations are often designed to help learners learn how to engage in professional practices (Fischer et al, 2022). To do so, learners gradually need to master transferring their relevant knowledge and skills to various practice situations.…”
Section: Representations Of Practice For Conceptualizing and Adapting...mentioning
confidence: 99%
See 1 more Smart Citation
“…In teacher education, instructional time with student teachers is limited (Bauer and Prenzel, 2012). Hence, identifying the most relevant teaching and learning events as core practices is highly advantageous (Grossman et al, 2018;Fischer et al, 2022). Educational research has identified a number of core practices that Review on evidence-based teaching practices for decomposition of practice: tutoring of small groups (A).…”
Section: Selection Of Evidence-based Practicesmentioning
confidence: 99%
“…Since professional knowledge guides visual processing, the knowledge limits of teachers often prevent them from noticing relevant events due to the transient flow of information represented in a video case (Chandler, 2004). Particularly, novice teachers need additional instructional support, either from learning scaffolds (such as prompts) or through representational scaffolds (such as salience in video cases), that guide visual processing and professional vision (Fischer et al, 2022). Thereto, theories of multi-media learning in cognitive psychology are of relevance for designing effective instructional support (Derry et al, 2014).…”
Section: Introductionmentioning
confidence: 99%